Neo-passing : performing identity after Jim Crow - Godfrey, Mollie, 1979-; Young, Vershawn Ashanti; Wald, Gayle, 1965-; Elam, Michele (University of Illinois Press, 2018)
"This volume seeks to theorize and explore the concept of "neo-passing," or the proliferation of passing in the post-Jim Crow moment. Why--in our "color-blind" or "post-racial" moment--is passing still of such literary and cultural interest? To answer this question, chapters in this book focus on a range of passing practices, performances and texts that are part of the emerging genre of what we call neo-passing narratives. Neo-passing narratives are contemporary narratives that depict someone being taken for an identity other than what s/he is considered really to be. That these texts are written, constructed, or produced at a time when passing should have passed reveals that the questions passing raises--questions about how identity is performed and contested in relation to social norms--are just as relevant now as they were at the turn of the twentieth century"--